Alcohol consumption patterns of the Hungarian general and Roma populations - Kurshed, Ali Abbas Mohammad; Vincze, Ferenc; Pikó, Péter; Kósa, Zsigmond; Sándor, János; Ádány, Róza; Diószegi, Judit (Frontiers in Public Health, 2023)
Harmful alcohol use is a significant public health problem worldwide, though alcohol-related burden affects certain populations and ethnic minorities disproportionally, the European Region being the most heavily affected and also putting an increased risk on Roma populations. This ethnic minority group is the largest and most vulnerable ethnic minority in Europe and Hungary as well. The present study aimed to describe and compare alcohol consumption behaviors of the Hungarian general and Roma populations using the Alcohol Use Disorders Identification Test (AUDIT), which provides a comprehensive view on alcohol consumption behavior. In addition, a decomposition analysis was performed when the multivariate logistic or Poisson regression model showed significant differences between the two samples. Our findings suggest that Roma people of our study sample experience more alcohol-related harm even when considering past problems. The decomposition analysis revealed that sex and relationship status differences act more intense among Roma than non–Roma when considering alcohol-related harm. Equalizing these differences would be expected to reduce the Hungarian general and Roma population’s alcohol-related harm frequency gap. Investigating alcohol-attributed harms at the ethnicity level provides important information to identify high-risk groups, thus to design and implement more targeted and accessible interventions for alcohol problems.